P16-S Database Search of High Mass Resolution Data - Sadygov, R. G. (The Association of Biomolecular Resource Facilities, 2007)
The work describes modifications to and application of Sequest database search algorithms to identify peptides from their high mass accuracy tandem mass spectra. We show the technical problems encountered when attempting to use high mass accuracy data with the original Sequest algorithm. To overcome the problems, modifications have been made to the algorithm. The modifications are such that the results from the unmodified and modified algorithms are the same for the unit mass accuracy data. The work presents advantages in terms of the speed and reduced memory requirements of the modified algorithm. We apply the modified algorithm to a dataset obtained from site-specific digestion of a set of known proteins. The results demonstrate the effect of high mass accuracy on such characteristics of the Sequest scoring as cross-correlation score and delta-Cn. Based on the correlations between the mass accuracy and the Sequest scores, we attempt to identify optimal conditions for the mass accuracy to be applied in the database searches. A comparative analysis with the dataset of the same proteins, but under unit mass accuracy conditions, will also be presented. We analyze results obtained from searches of the spectra against the reversed databases under the high mass accuracy conditions.